PENGARUH CONTENT CREATOR PADA APLIKASI REEL INSTAGRAM DALAM MENINGKATKAN INOVASI GENERASI MUDA - Ni luh juliantari Ni luh juliantari; Anak Agung Elik Astari Anak Agung Elik Astari; Ni Luh Indiani Ni Luh Indiani (Nusantara Hasana Berdikari, 2022)
This study aims to determine the effect of content creators on the Instagram Reel application in increasing the innovation of the younger generation. The population and sample in this study were Instagram reel users in Denpasar in September 2022. Data collection was carried out by distributing research respondents. Data analysis was performed using multiple linear regression analysis. The results of the analysis show that content creators have a positive and significant effect on young generation innovation, Instagram reels have a positive and significant impact on young generation innovation. The implication of this research is that the younger generation must maintain and improve their creativity in creating new ideas and must increase innovation in the future. Then for further researchers to add other variables, which have not been included in this study in order to expand this research.